DETERMINANTS OF THEORY TECHNOLOGY OF ACCEPTANCE MODEL (TAM) IN MEASURING EDUCATORS’ CONTINUANCE INTENTION OF LEARNING MANAGEMENT SYSTEM (LMS) (Journal of Technology and Operations Management, 2016)
The purpose of the study was to examine the individual context in terms of educators’ continuance intention of using Learning Management System (LMS). Technology Acceptance Model (TAM), as a supportive framework is used to measure the influence of the educators’ experience towards determinant of Information System (IS) continuance intention for using LMS services. This study was conducted at the University Teknologi Mara (UiTM) among educators. The stratified sampling method was used in sample selection for this study. Survey data collected from 69 respondents were examined using Statistical Package for the Social Sciences Version 21 (SPSS 21). The cross sectional data were collected through a survey and the data analyzed by means of factor analysis, correlation and multiple regression analysis. The findings indicate that perceived usefulness and perceived ease of use were significantly direct determinant of users’ continuance intention.